2001
DOI: 10.1046/j.1523-1747.2001.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Organotypic Cocultures with Genetically Modified Mouse Fibroblasts as a Tool to Dissect Molecular Mechanisms Regulating Keratinocyte Growth and Differentiation

Abstract: Organotypic cocultures of keratinocytes and fibroblasts generate a normal epidermis irrespective of the species and tissue origin of fibroblasts. The use of mouse fibroblasts and human keratinocytes facilitates the identification of the origin of compounds involved in epidermal tissue reconstitution and growth regulation. Moreover, the functional significance for the keratinocyte phenotype of genetically modified fibroblasts from transgenic or knockout mice, even those exhibiting an embryonic lethal phenotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 29 publications
(45 reference statements)
3
91
1
Order By: Relevance
“…20 -22 Fibroblasts, which are included in these models, 20 -22 promote keratinocyte proliferation and differentiation via the secretion of factors such as KGF and GM-CSF. 29,30 In our model, we showed that addition of fibroblast-derived KGF to the skin equivalents in combination with EGF results in the correct morphological and molecular characteristics of normal human skin, including the absence of the psoriasis-associated proteins SKALP, hBD-2, and cytokeratin 16. It should be noted that the cytokines used in our model might have different effects, both qualitatively and quantitatively, in skin equivalent models containing fibroblasts.…”
Section: Discussionmentioning
confidence: 80%
“…20 -22 Fibroblasts, which are included in these models, 20 -22 promote keratinocyte proliferation and differentiation via the secretion of factors such as KGF and GM-CSF. 29,30 In our model, we showed that addition of fibroblast-derived KGF to the skin equivalents in combination with EGF results in the correct morphological and molecular characteristics of normal human skin, including the absence of the psoriasis-associated proteins SKALP, hBD-2, and cytokeratin 16. It should be noted that the cytokines used in our model might have different effects, both qualitatively and quantitatively, in skin equivalent models containing fibroblasts.…”
Section: Discussionmentioning
confidence: 80%
“…It was assumed that fibroblasts influence keratinocytes through diffusible factors that act in a paracrine fashion to regulate keratinocyte growth and differentiation (Tuan et al, 1994;Luger and Schwarz, 1995;Garner, 1998;Smola et al, 1998). More recently it has been shown that fibroblasts and keratinocytes interact through a double paracrine regulatory pathway that involves upregulation of interleukin-1 in keratinocytes, which then stimulates keratinocyte growth factor expression in cocultured fibroblasts (Maas-Szabowski et al, 2001). This correlates with our finding that skin keratinocytes upregulate K19 expression only in combination with alveolar or sulcular gingival fibroblasts, and upregulate K4 and K13 only in combination with alveolar fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes from mice in which c-Jun has been conditionally inactivated in the epidermis show decreased expression of epidermal growth factor receptor (EGFR) and its ligand HB-EGF, proliferate poorly, and differentiate at a faster rate (Zenz et al, 2003). In addition, AP-1 is involved in a paracrine loop whereby IL-1 in keratinocytes induces c-Jun in fibroblasts to produce keratinocyte growth factor (KGF) and granulocyte-macrophage colony-stimulating factor (GM-CSF), both of which feed back on keratinocytes to promote cell growth and differentiation (Szabowski et al, 2000;Maas-Szabowski et al, 2001). AP-1 is also involved in the expression of cornified envelope precursors, including loricrin (DiSepio et al, 1995) and involucrin (Takahashi and Iizuka, 1993;Welter and Eckert, 1995), as well as TGase1 (Liew and Yamanishi, 1992;Yamada et al, 1994).…”
Section: Ap-1mentioning
confidence: 99%